2022
DOI: 10.1093/jxb/erac250
|View full text |Cite
|
Sign up to set email alerts
|

Altered collective mitochondrial dynamics in the Arabidopsismsh1mutant compromising organelle DNA maintenance

Abstract: Mitochondria form highly dynamic populations in the cells of plants (and all eukaryotes). The characteristics and benefits of this collective behaviour, and how it is influenced by nuclear features, remain to be fully elucidated. Here, we use a recently developed quantitative approach to reveal and analyse the physical and collective "social" dynamics of mitochondria in an Arabidopsis msh1 mutant where organelle DNA maintenance machinery is compromised. We use a newly created line combining the msh1 mutant wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…Plant mitochondria undergo fission and fusion to form transient networks which could allow the exchange of genetic information. To test this hypothesis, Chustecki et al (2022) used msh1 mutants with defective DNA repair, and showed that mitochondrial interactions increased, revealing a link between the physical and genetic behavior of mitochondria.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Plant mitochondria undergo fission and fusion to form transient networks which could allow the exchange of genetic information. To test this hypothesis, Chustecki et al (2022) used msh1 mutants with defective DNA repair, and showed that mitochondrial interactions increased, revealing a link between the physical and genetic behavior of mitochondria.…”
mentioning
confidence: 99%
“…In plants, MSH1, a MutS homolog, is a protein that plays a role in organellar genome maintenance, including homologous recombination ( Abdelnoor et al , 2003 ), and in msh1 mutants the mitochondrial mutations accumulate ( Wu et al , 2020 ). By analyzing mitochondrial dynamics in the msh1 mutant and comparing it with the wild type, Chustecki et al (2022) aimed to answer the question of whether mitochondria interact differently when they have compromised mtDNA integrity. Because mitochondria in msh1 mutants accumulate damage, the authors hypothesized that they would frequently interact with each other, possibly to acquire an intact template for homology-based DNA repair.…”
mentioning
confidence: 99%
See 3 more Smart Citations